Julie Of The Wolves - George, Jean Craighead; Schoenherr, John (New York Harper Trophy, 1972)
While running away from home and an unwanted marriage, a thirteen-year-old eskimo girl becomes lost on the north slope of alaska and is befriended by a wolf pack
American Corner
Winner Of The John Newbery Medal, 1973
11
Keywords: English Fiction; English Stories; Eskimoes -- Fiction; Wolves -- Fiction